2013
DOI: 10.1073/pnas.1314754110
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for Spt5-mediated recruitment of the Paf1 complex to chromatin

Abstract: Polymerase associated factor 1 complex (Paf1C) broadly influences gene expression by regulating chromatin structure and the recruitment of RNA-processing factors during transcription elongation. The Plus3 domain of the Rtf1 subunit mediates Paf1C recruitment to genes by binding a repeating domain within the elongation factor Spt5 (suppressor of Ty). Here we provide a molecular description of this interaction by reporting the structure of human Rtf1 Plus3 in complex with a phosphorylated Spt5 repeat. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 51 publications
5
102
0
1
Order By: Relevance
“…The present structural snapshot of the RNA capping enzyme Pct1 bound to Spt5 CTD sequence TPAWN extends insights from the recently reported crystal structure of a human Spt5 CTR binding protein (Wier et al 2013): the Plus3 domain of Rtf1 bound to a phosphorylated CTR peptide SGSRT P PMYGSQ. Figure 6 shows an alignment of the Spt5 ligands from the two structures, superimposed at their respective Thr-Pro dipeptides.…”
Section: Structural Plasticity Of the Spt5 Ctdsupporting
confidence: 74%
See 2 more Smart Citations
“…The present structural snapshot of the RNA capping enzyme Pct1 bound to Spt5 CTD sequence TPAWN extends insights from the recently reported crystal structure of a human Spt5 CTR binding protein (Wier et al 2013): the Plus3 domain of Rtf1 bound to a phosphorylated CTR peptide SGSRT P PMYGSQ. Figure 6 shows an alignment of the Spt5 ligands from the two structures, superimposed at their respective Thr-Pro dipeptides.…”
Section: Structural Plasticity Of the Spt5 Ctdsupporting
confidence: 74%
“…The proline is in the trans conformation in both structures. In the case of Rtf1, the Spt5 interface is dominated by hydrogen bonding contacts to the phosphate group of the Spt5 ligand, consistent with the fact that threonine phosphorylation is required for Rtf1 binding to Spt5-CTR (Wier et al 2013). In contrast, Pct1 makes no contacts with the Spt5 threonine side chain and its binding to Spt5 is antagonized by threonine phosphorylation.…”
Section: Structural Plasticity Of the Spt5 Ctdmentioning
confidence: 53%
See 1 more Smart Citation
“…2, the most likely candidate for the Rtf1 coactivator was the PAF1C. Based on a recent study in S. cerevisiae (35), DSIF might also be a candidate for the Rtf1 coactivator, although DSIF did not comigrate with the coactivator activity at the phosphocellulose step. To explore these possibilities, the PAF1C was immunodepleted from HeLa cell NE using antibodies against the PAF1C.…”
Section: Resultsmentioning
confidence: 98%
“…In in vitro transcription assays using S. cerevisiae cell extracts and a naked DNA template, Rondon et al (16) showed that paf1⌬ and cdc73⌬ cell extracts were defective in elongation, whereas rtf1⌬ and leo1⌬ cell extracts were not; however, recent papers have shown that S. cerevisiae Rtf1 is critical for the recruitment of the PAF1C (20,34,35). The conserved Plus3 domain of Rtf1 interacts with the phosphorylated form of Spt5, the large subunit of DSIF, and thereby recruits the other PAF1C subunits to actively transcribed genes (5,(35)(36)(37)(38)(39). In higher eukaryotes, we used a human in vitro transcription system to show that the PAF1C cooperates with DSIF and Tat-SF1 to promote transcription elongation on a naked DNA template (13).…”
mentioning
confidence: 99%